Similarity between Piaractus mesopotamicus, Colossoma macropomum and their interspecific hybrids - Costa, Adriano Carvalho; Serafini, Moacyr Antônio; Neto, Rafael Vilhena Reis [UNESP]; Santos, Priscilla Freitas; Marques, Letícia Ribeiro; de Rezende, Isabel Rodrigues; Mendonça, Maria Andreia Corrêa; Allaman, Ivan Bezerra; de Freitas, Rilke Tadeu Fonseca (Elsevier, 2020)
This study aimed to estimate the genetic similarities between Pacu (Piaractus mesopotamicus), Tambaqui (Colossoma macropomum) and their intraspecific hybrids. Sixty Pacu, Tambaqui, Tambacu and Paqui specimens were used, which were anaesthetised (benzocaine 60 mg/L), weighed and analysed for morphometric body parameters. Afterwards the animals were processed to obtain the weight and yield of viscera, head, fillet, ribs, skin and residue (backbone and fins). In order to carry out the clustering analysis the morphometric ratios, and weights and yields of the products and by-products obtained were determined. The Euclidean distances between groups were calculated based in the data collected, and the clustering methods Simple, Ward, Complete, Average, Median and Centroid were tested through cophenetic correlation. In general, all the clustering methods presented high cophenetic correlation (r > 0.70), with the lowest value by the Simple (0.7369) and the highest by the Average (0.7890) methods. In all dendrograms, similar fusion behaviour was observed, indicating a greater similarity between the Pacu and Paqui groups and between Tambaqui and Tambacu groups, only the metrics (maximum values) and the cut-off point varying between the different methods. The Average clustering method indicated a greater similarity of the hybrids with the species used as the female parent. Therefore, in a hybridisation strategy, it should be verified in which species, Pacu or Tambaqui, the characteristic of interest is best expressed before defining the maternal parent.
Keywords: Animal science, breeding; Multivariate statistics; Round fish